Systems of Periodization Developed and Used to Study the Urnfield Period in Slovakia - Furmánek, Václav; Mitáš, Vladimír (Fundacja Rzeszowskiego Ośrodka Archeologicznego, 2016)
The authors offer review of systems of periodization dealing with issues of the Urnfield Period in Slovakia. They refer to the general principles on which chronological and synchronisation models are based, but also on their creation and use. The elements of current periodization of the Bronze Age have been evolving in Europe since the late 19th and the early 20th centuries (O. Montelius, P. Reinecke), and these systems were further developed. Specifically, the authors deal with more than twenty systems of periodization and synchronisation, which are gradually discussed and then introduced schematically. These systems were developed by Slovak researchers (M. Novotna, V. Furmanek, S. Demeterova and others) during the 20th and the early 21st centuries. In modified form, these systems are being used to study the Urnfield Period up to the present day.
This contribution is the result of the project implementation: VEGA Project no. 2/0091/16. Translation: Dana Marková.
Keywords: Slovakia; Urnfield Period; Chronology; Periodization; Synchronisation